Pengaruh Kepemimpinan Situasional dan Budaya Organisasi terhadap Team Work serta Implikasinya pada Kinerja Organisasi - Nana Suhana (Kontigensi : Jurnal Ilmiah Manajemen, 2017)
The purpose of this study is to investigate and analyze: (1) how the condition of situational leadership,organizational culture, team work and organizational performance. (2) how the influence of situationalleadership scale effect on Team Work. (3) how the influence of organizational culture effect on Team Work.(4)how much the Situational Leadership and Organizational Culture influence on Team Work (5) how much theimplications of Team Work on Organizational Performance in Office of County and City of West Java Province.The result showed: (1) Implementation Situational, Leadership, Organization Culture, Team Work andOrganizational Performance accurate on Departments in good classification storey; level.(2) Covariancevariables average Situational Leadership could predictability Situational Leadership of 62.10%, the effect ofpartial structurally Situational Leadership to Team Work of 41.95%. (3) Covariance variable averageOrganizational Culture could predictability Organizational Culture of 76.50%., Organizational Culturestructurally partial effect on Team Work of 30.87%. (4) Situational leadership structurally and CulturalOrganization Team Work simultaneous influence of 72.82%. The remaining balance of 27.18% is the mistakeof excluding variable indicators research (5) Team Work Covariance variables, the average could predictabilitythe Team Work of 81.85%. Team Work partially structurally influence the performance of the Organization of74.38%, the remaining balance of 25.62% is the mistake of the variable indicators outside the study (6)Covariance Organizational Performance variables, the average could affect Organizational performance of76,95%.